Phosphate Reduction in Laundry Wastewater Using Activated Coffee Grounds and Fly Ash as Adsorbents - Rony Pasonang Sihombing; Christianti Christianti; Nabila Dwi Nur Ramadhani; Nadya Zafirra Martadinata; Alfiana Adhitasari; Dianty Rosirda Dewi Kurnia (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2025)
The growth and development of the population have significantly accelerated economic progress within society. Consequently, many new businesses have emerged, including commercial laundry services. One of the substances found in laundry wastewater, phosphate can cause eutrophication, which disrupts the balance of aquatic ecosystems. One method that can be developed to address this issue is adsorption technology. The aim of this research was to lower the phosphat content and to meet the Regulation of the Minister of Environment of the Republic of Indonesia No. 5 of 2014. The increasing number of coffee shops generates coffee grounds that have the potential to be processed into activated carbon. Additionally, fly ash a by-product of coal combustion contains silica and can be used as an adsorbent. The activated carbon is activated using 0.1 N NaOH and combined with fly ash in various compositions: 2:8, 4:6, 5:5, 6:4, and 8:2. Besides the variation in composition, contact time is also varied 30 minutes, 60 minutes, 90 minutes, 120 minutes, and 150 minutes. The observed parameters include pH and phosphate concentration at each contact time. The research results show that the optimal composition is 0.2AC:0.8FA with the highest phosphate removal efficiency of 60.3% at 150 minutes contact time and a pH of 7.1. However, the final phosphate concentration has not yet met the quality standard of 2 mg/L set by the Regulation of the Minister of Environment of the Republic of Indonesia No. 5 of 2014.